The interpositional bypass with a parietal branch of superficial temporal artery graft for symptomatic atherosclerotic anterior cerebral artery stenosis or occlusion - Tai, Chuyang; Ling, Cong; Huang, Tengchao; Zhang, Baoyu; Yang, Yang; Wei, Lei; Wu, Haiwan; Mo, Ni; Wang, Hui; Chen, Chuan (Frontiers in Neurology, 2024)
Background: For nonmoyamoya patients with anterior cerebral artery (ACA) stenosis or occlusion, whether direct revascularization of the ACA territory can prevent stroke is still unclear. The objective of this study was to investigate the efficacy and safety of a parietal branch of superficial temporal artery-interposed superficial temporal artery-to-ACA bypass (PISAB) for preventing stroke in patients with symptomatic atherosclerotic ACA stenosis or occlusion (SAASO). Methods: We retrospectively analyzed the data from patients with SAASO who had undergone PISAB in our center between April 2016 and November 2021. The rates of patency, satisfaction (revascularization grades A and B) of bypass, perioperative complications, recurrence of ischemic stroke, changes in bypass flow, and improvements in cerebral blood perfusion were analyzed. Results: A total of 19 SAASO patients were involved in this study. Sixteen out of 19 (84.2%) patients were free from any cerebral ischemic events after surgery. Only 3 patients (15.8%) had recurrent stroke postoperatively. Two (10.5%) surgery-related complications occurred, including hyperperfusion syndrome and minor stroke. No skin ischemic complications occurred. The average follow-up period was 50.6 ± 18.3 months. The flow rate of the bypass was significantly increased half a year after surgery (56.2 ± 8.0 ml/min vs. 44.3 ± 5.3 ml/min, P <.001). The ratio of ipsilateral/contralateral mean transit time in the superior frontal gyrus was decreased significantly after bypass (1.08 ± 0.07 vs. 1.23 ± 0.05, P <.001) and continued to decrease 6 months after surgery (1.05 ± 0.04 vs. 1.08 ± 0.07, P =.002). The patency rate of PISAB was 94.7% (18/19) 2 years after surgery. The satisfaction rate of bypass was 89.5% (17/19). Conclusion: The results of this study indicate that PISAB, as a safe superficial bypass, can effectively reduce the risk of stroke in SAASO patients. More precise conclusions will require randomized control studies.